Hazard conditions of water deficit and excess events in the Santa Fe dairy basin, period 1959-2023 (FAVE Sección Ciencias Agrarias, 2025)
In the past few years, the Argentine agricultural and livestock production sector has suffered millions of dollars in losses due to the impact of events involving excesses and deficits in water. Analyzing the frequency and intensity of these phenomena is necessary and becomes crucial for better understanding their extent across the territory. In response, this article describes the methodology of an indicator that analyzes the hazard conditions (Ip) and climate variations of the aforementioned events in the central dairy basin of Santa Fe during the period from 1959 to 2023. To achieve this, data from strategically located meteorological stations were used, covering a geographically diverse area to identify climate variations within the study region. The Ip is constructed based on the Standardized Precipitation-Evapotranspiration Index (SPEI) and a frequency analysis of probabilities, which are then categorized according to their hazard level. The Ip revealed a trend of higher probability of occurrence for water deficit events over excess events, reflecting a shift towards drier conditions in the region. Recognizing risk conditions enables the design of preventive policies aimed at reducing and mitigating the impact of such events on the territory, population and production.
Keywords: Dairying; SPEI; droughts; floods